Low-risk prenatal care: difficulty for pregnant women to perform prenatal care with the Nurse (Research, Society and Development, 2020)
The present study aimed to analyze the obstacles in carrying out low risk prenatal care with the nurse. To this end, a descriptive exploratory study with a qualitative approach was carried out. Thirty pregnant women who underwent low-risk prenatal care at the Women's Health House and the Comprehensive Medicinal Clinic of a Teaching Hospital participated in the study, who responded to a recorded interview, and the data analysis was carried out through the characterization of the clientele and the categorization of interview responses. In view of the analysis, it was possible to discuss, and the following results were obtained, predominance of the age group from 21 to 25 years old 36.6%, education 70% have completed High School, 50% have a stable union, have no children 43, 3%, and 26.6% and were in the 20th gestational week. The following study categories were created: 1) The culture of prenatal care by the medical professional, 2) The organization of the Network in directing from the patient to areas where it is not the nurse who performs low risk prenatal care and 3) Ignorance of the nurse's role in caring for low risk prenatal care. In view of the above, it was possible to conclude that the obstacles in carrying out low-risk prenatal care between the pregnant woman and the nurse are related to the process of referral flows and free access to the structure of the service network to carry out this activity in the municipality, maintaining the culture of medical care during consultations, which contributes to the fact that pregnant women are unaware of the role of nurses in carrying out low-risk prenatal care.